Significance and Necessity of Statistics on Wood Waste in Circular Economy Project Implementation at Forest-Industry Complex - A. A. Danilov; N. N. Yashalova (Вестник Российского экономического университета имени Г. В. Плеханова)
Production waste in forest-industry complex of economy is an important ecologic problem, which could be resolved by business entities changing-over to circular economy. Statistics on the amount of wood waste is essential for realizing the concept of closed-cycle economy in forest-industry complex. The article provides information about volumes of wood waste in the Russian Federation. The authors studied nature of wood waste and its classification, analyzed theoretical experience in estimating the amount of wood waste, provided calculations of wood waste being formed in home forest-industry complex. Priority trends in the field of wood waste recycling are demonstrated. The article can be interesting both for scientists and practical experts studying problems of forest-industry complex changing-over to the closed-cycle economy.